Walking through doorways differentially affects recall and familiarity. - Seel, Sabrina V.; Easton, Alexander; McGregor, Anthony; Buckley, Matthew G.; Eacott, Madeline J. (British Journal of Psychology, 2019)
Previous research has reported that walking through a doorway to a new location makes memory for objects and events experienced in the previous location less accurate. This effect, termed the location updating effect, has been used to suggest that location changes are used to mark boundaries between events in memory: memories for objects encountered within the current event are more available than those from beyond an event boundary. Within a computer‐generated memory task, participants navigated through virtual rooms, walking through doorways, and interacting with objects. The accuracy and their subjective experience of their memory for the objects (remember/know and confidence) were assessed. The findings showed that shifts in location decreased accurate responses associated with the subjective experience of remembering but not those associated with the experience of knowing, even when considering only the most confident responses in each condition. These findings demonstrate that a shift in location selectively impacts recollection and so contributes to our understanding of boundaries in event memory.